Komparasi Metode Naïve Bayes dan C45 pada Prediksi Pelanggan Deposito Berjangka - Meilany Nonsi Tentua (Universitas PGRI Yogyakarta, 2022)
Determining product customers in the banking world in marketing products such as time deposit products is a problem. This study aims to compare the methods in developing a predictive model for time deposit subscriptions with direct marketing from Portuguese banking institutions. This marketing is based on phone calls, by entering contact information data made to the client to get a